The wedding crasher and the cowboy - Bielman, Robin (Amara, an imprint of Entangled Publishing, LLC, 2021)
Kennedy Martin is spurred into action when her ex calls her, days before his wedding, to express his doubts about the upcoming marriage. She needs to convince him that marrying his fiancée is the right choice, and so she crashes the pre-wedding in order to talk to him. As if that situation isn't difficult enough--she runs into Maverick Owens, her old college nemesis, and is forced to pretend she's with him so she can attend all the events.